CYBERSPACE RISKS AND THREATS TO CRITICAL INFORMATION INFRASTRUCTURE - Constantin MINCU; Gruia TIMOFTE (Annals: Series on Military Sciences, 2011)
Critical infrastructures are those physical and cyber-based systems essential to the minimal economy and government operations. They include but are not limited to, telecommunications, energy, banking and finance, transportation, water systems and emergency services, both governmental and private. Many of the national critical infrastructures have historically been physically and logically separate systems that had little interdependence. As a result of progress in communication and information technology and the necessity of improved efficiency, however, these infrastructures have become increasingly automated and interlinked. The same progress has created new vulnerabilities to equipment failure, human error, weather and other natural causes, physical and cyber-attacks. Addressing these vulnerabilities will necessarily require flexible, evolutionary approaches that span both the public and the private sectors, and protect both domestic and international security.